The new woman and technologies of speed in fin-de-siècle literature / Eva Chen. - Chen, Eva, 1980- (Oxford scholarship online., 2024)
This is a literary study on the New Woman's interaction with modern speed culture through use of the typewriter and the bicycle. These technologies of speed are among the earliest to be associated with middle-class women, exposing them to the discipline of mechanized speed while allowing for the construction of a new machine-savvy, sped-up, and energized female subjectivity. By examining New Woman literature penned by George Gissing, H.G. Wells, Grant Allen, Geraldine Edith Mitton, and Mrs Edward Kennard, and stories and comments published in popular magazines, this book examines how mechanized speed works on the New Woman typist and cyclist, first as discipline and control (in typewriting), then as commodity and conspicuous display (in cycling), and finally as rejuvenation, stimulation, and active thrill.